Victimology Review of Online Gambling Perpetrators in the Perspective of Indonesian Criminal Law - Alvan Rahfiansyah Lubis (HM Publisher, 2022)
Victimology is a science used to study victims. Following its meaning Victimology comes from the Latin word victima which means victim and logos which means scientific knowledge or study. The ease of access to gambling websites lures many people to try and get involved with online gambling. This study aims to discuss the victimization review of online gambling perpetrators from the perspective of Indonesian criminal law. This research is sociological legal research. Victimology in this regard is defined as a scientific study of victimization, including the relationships between victims and offenders, the interaction between victims and the criminal justice system. In conclusion, gambling is not justified regardless of its form in terms of playing cards, lottery, or slot gambling. Everyone involved in gambling, whether as a bookie or a gambler, must face legal consequences related to his actions.